ChemInform Abstract: Rapid Estimation of Beta‐Lactam Antibiotics in Biological Fluids. Issue 49 (December 2015) - Joris, Bernard; Degelaen, Jacques; Klein, Frank; Frere, Jean‐Marie
Abstract: Review: 12 refs.